2019
DOI: 10.1038/s41529-019-0088-z
|View full text |Cite
|
Sign up to set email alerts
|

Reliable electrochemical phase diagrams of magnetic transition metals and related compounds from high-throughput ab initio calculations

Abstract: Magnetic transition metals (mTM = Cr, Mn, Fe, Co, and Ni) and their complex compounds (oxides, hydroxides, and oxyhydroxides) are highly important material platforms for diverse technologies, where electrochemical phase diagrams with respect to electrode potential and solution pH can be used to effectively understand their corrosion and oxidation behaviors in relevant aqueous environments. Many previous decades-old mTM-Pourbaix diagrams are inconsistent with various direct electrochemical observations, because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 130 publications
2
58
2
Order By: Relevance
“…In the reaction energy calculation, we neglect the zero-point energy (E ZPE ) and the integrated heat capacity from 0 to 298.15 K (δH) for both solids and gases by assuming that the differences in these quantities between reactants and products are negligible at room temperature. Previous studies in the literature show that E ZPE and δH of solids and gases are comparable [39][40][41] , but we note that estimation of E ZPE and δH is possible, albeit expensive, with phonon or molecular dynamics calculations, and a systematic approach towards these that can further improve our approach merits a study in its own right.…”
Section: Applicationsmentioning
confidence: 80%
“…In the reaction energy calculation, we neglect the zero-point energy (E ZPE ) and the integrated heat capacity from 0 to 298.15 K (δH) for both solids and gases by assuming that the differences in these quantities between reactants and products are negligible at room temperature. Previous studies in the literature show that E ZPE and δH of solids and gases are comparable [39][40][41] , but we note that estimation of E ZPE and δH is possible, albeit expensive, with phonon or molecular dynamics calculations, and a systematic approach towards these that can further improve our approach merits a study in its own right.…”
Section: Applicationsmentioning
confidence: 80%
“…2,28 In the reaction energy calculation, we neglect the zero-point energy (E ZPE ) and the integrated heat capacity from 0 K to 298.15 K (δ H) for both solids and gases by assuming that the differences in these quantities between reactants and products are negligible at room temperature. Previous studies in the literature show that E ZPE and δ H of solids and gases are comparable, 28,33,34,41 but we note that estimation of E ZPE and δ H is possible, albeit expensive, with phonon or molecular dynamics calculations, and a systematic approach towards these that can further improve our approach merits a study in its own right.…”
Section: Validationmentioning
confidence: 75%
“…We note that NiO and/or Ni(OH) 2 was often observed to be stable at pH 5∼15 in experiment. 33,34 This is probably because in practical applications the Ni aqueous ion concentration is much higher than the conventional one ( 10 1.60 V in OER. [36][37][38] In experiment, the formation of high-valence iridium oxides, e.g.…”
Section: Validationmentioning
confidence: 99%
“…The previous studies have indicated that the DFT is among the most versatile and popular methods to investigate electronic structure of solids . The optimization of bulk FeS 2 and all surface relaxation calculations were performed with the Perdew–Burke–Ernzerhof (PBE) density functional as implemented in the Dmol 3 code .…”
Section: Calculation Methodsmentioning
confidence: 99%